2018
DOI: 10.4317/jced.54925
|View full text |Cite
|
Sign up to set email alerts
|

Clear aligners effects on aesthetics: evaluation of facial wrinkles

Abstract: BackgroundTo evaluate the facial aesthetic effects of orthodontic treatment performed with clear aligners and to compare it to an untreated control group, on lower third facial ageing in adult patients through the use of the Wrinkle Severity Rating Scale (WSRS) at the beginning (T0) and at the end (T1) of the study period.Material and MethodsA clear aligners treated group (TG) of 68 patients was compared to a control group of 33 untreated patients (UG). Each group was divided in 2 subgroups according to age: s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The use of aligner tray seaters can make the aligners fit more closely with the tooth surface and achieve the intended orthodontic force system [ 21 ]. At the same time, the masticatory muscles are exercised with aligner tray seaters for patients who have had extracted premolars or molars, and the unjoyful appearance of “bracket face” can also be ameliorated [ 22 ]. However, our finding shows that the use of aligner tray seaters will increase the probability of attachment loss, which is in contrast with the findings of Huang et al [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of aligner tray seaters can make the aligners fit more closely with the tooth surface and achieve the intended orthodontic force system [ 21 ]. At the same time, the masticatory muscles are exercised with aligner tray seaters for patients who have had extracted premolars or molars, and the unjoyful appearance of “bracket face” can also be ameliorated [ 22 ]. However, our finding shows that the use of aligner tray seaters will increase the probability of attachment loss, which is in contrast with the findings of Huang et al [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…19 To avoid the use of an additional retention appliance, the final aligner can be used for three months after the end of the treatment to retain the corrected tooth positions. 20 Some limitations of this report should also be considered. Although the results were encouraging, there is a need for evidence to draw guidelines for clinical practice and compare the perceptions of the patient's pain and discomfort for the correction of AC with clear aligner, FA, and RA treatments.…”
Section: Discussionmentioning
confidence: 93%
“… 19 To avoid the use of an additional retention appliance, the final aligner can be used for three months after the end of the treatment to retain the corrected tooth positions. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, VFRs were dominant in other countries [ 7 , 19 ]. It is worthy of mention that recently, it has been reported that clear aligners can be used for retention, and one of their advantages is a global improvement of facial aesthetics [ 21 ].…”
Section: Discussionmentioning
confidence: 99%